The appearance of renewable energy sources in the settlement development documents of local authorities in Jász-Nagykun-Szolnok County - Kozma, Gábor; Monyók, Bence (Acta Geographica Debrecina Landscape & Environment series, 2021)
In recent decades, several new trends can be observed in the field of energy management, one of which is the increase of the role of renewable energy sources. As a result of this fact, local authorities in Hungary have also devoted increasing attention to this question in recent years. The first step of their interventions is the drawing up of the appropriate development documents, relying on which specific steps/investments can also take place later. In the spirit of the above, the objective of the present paper is to analyse the development documents of local authorities in Jász-Nagykun-Szolnok County. The most important findings of the study could be summarised as follows. Firstly the Integrated Settlement Development Strategies prepared for the period 2014 to 2020 dealt with the topic of renewable energy sources in much more detail than earlier documents. Secondly from the various renewable energy sources, the development document devoted most attention to solar and geothermal energy and thirdly the appearance of renewable energy sources in the development documents shows a close link with the size of the settlements.